PENGEMBANGAN LEMBAR KEGIATAN PESERTA DIDIK DALAM PEMBELAJARAN MEMBACA PERMULAAN PADA PESERTA DIDIK KELAS 1 SDN JANTI - Innany Mukhlishina; Cahyaningtyas, Aura (PGSD UNIKA SANTU PAULUS RUTENG, 2023)
This study aims to develop student activity sheets (LKPD) for effective beginning reading for grade 1 students at Janti Public Elementary School. The development method used is the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). Needs analysis is carried out to understand the challenges and needs of students in learning to read beginning. Based on this analysis, LKPD was developed taking into account appropriate learning approaches and a variety of activities that support conceptual understanding and learning differentiation. LKPD was then implemented in class 1 learning at Janti State Elementary School. Data collection was carried out through observation, interviews, and evaluation tests. The collected data were analyzed by qualitative description. the results of the study show that the use of LKPD in early reading learning can increase student engagement, conceptual understanding, and reading skills. Students show higher interest and motivation in learning by using LKPD. In addition, the variety of activities in LKPD helps facilitate independent learning and differentiation of learning to meet the individual needs of students.Based on these findings, it can be concluded that the development of LKPD as a media for learning early reading has the potential to increase the effectiveness of learning and reading skills of grade 1 students. This research makes a practical contribution in developing learning strategies that suit the needs of students in learning to read beginning. The implication of this research is the importance of paying attention to the design and development of appropriate worksheets to facilitate effective early reading learning at the 1st grade level of elementary school.